Is Gross Capital Formation And Gross Savings A Component In Saudi Arabia's Economic Growth? - Simranjeet Kaur (UIN Mataram, 2021)
Gross Capital Formation and Gross Savings are important drivers of a country's Gross Domestic Product growth. Gross Capital Formation is the sum of gross additions to fixed assets and stock change whereas Gross Savings are excess of Disposable Income over consumption of the Nation. Savings promotes investments and which directly accelerates the investments. The purpose of this study is to Examine the relation and impact of Gross Capital formation and Gross saving on the Saudi Arabia's GDP. For the purpose of the research study secondary data related to economy of Saudi Arabia was gathered. 20 years data from the period 2000 to 2019 were considered and several key tests using SPSS were carried out, including correlation and multiple regression to examine statistical relevance of capital formation and savings on the Gross Domestic Product. The conclusion of this study is that Gross Domestic Product of Saudi Arabia is highly dependent upon Gross Capital Formation and Gross Savings of the Country and there found the positive linear relationship between GCF and growth of GDP.